Unraveling the Diversity of Trajectories and Drivers of Global Agricultural Land Abandonment - Alexander V. Prishchepov; Florian Schierhorn; Fabian Löw (Land, 2021)
The world is facing a looming scarcity of land necessary to secure the production of agricultural commodities and experiencing competition from other land uses [...]